CORPORATE SOCIAL RESPONSIBILITY DALAM DUNIA OTOMOTIF DAN STRATEGI BRAND - Yenni Martok (MTU PRESS, 2024)
Understanding how corporate social responsibility (CSR) is implemented in business growth and societal development is the goal of this study. In order to maximize economic gains, it is required to advance social welfare, which includes stakeholders in the companies. Certain businesses now require more corporate social responsibility (CSR) while developing their brand strategies and when it comes to corporate governance and their obligation to protect the environment. Additionally, the company's needs for sustainable expansion have increased. A complex and diverse supply chain system and a multitude of production processes are characteristics of the automotive industry. Automotive firms fully leverage their cross-industry and internal strengths. At this point, CSR will turn into a means of giving back to the community, establishing the framework for long-term brand growth and paying greater attention to social resources. It will result in brand strategies and how the automotive industry's CSR relates to them